Pan-cancer analysis identifies tRNA modification enzyme CTU2 as a novel tumor biomarker and its role in immune microenvironment - Jiaojiao Wang; Chang Gao; Junyi Zhang; Huahong Luo; Siqi Dai; Jianwei Wang; Jianwei Wang (Frontiers in Immunology)
BackgroundRecent studies have highlighted dysregulated tRNA modifications in the reprogramming of tumor translation. Cytosolic thiouridylase subunit 2 (CTU2) is an essential and conserved enzyme that modifies tRNA at the wobble position. However, the relationship between CTU2 expression and various cancer types remains insufficiently explored.MethodsPan-cancer data from TCGA, GEO, and CPTAC were used to analyze CTU2 expression and its prognostic value. Single-cell and spatial transcriptomic analyses were performed to identify CTU2’s cell-type labels and distribution. The TCGA microRNA database was used to explore the expression patterns of CTU2-modified tRNAs and their prognostic significance. TIMER2.0, ESTIMATE, and TIP were employed to analyze the correlation between CTU2 expression, immune infiltration, and immunotherapy response. GSEA and Depmap databases were conducted to explore signaling pathways related to CTU2 expression. Drug sensitivity related to CTU2 was assessed using CMap and GDSC-V2. The oncogenic roles of CTU2 were validated in vitro and in vivo. Genomic alterations, public ChIP-seq data, dual-luciferase assays, and EMSA were employed to investigate the upstream regulatory mechanisms regulating CTU2.ResultsCTU2 and its modified tRNA, particularly tRNA-Lys-TTT, are differentially expressed across various tumor types, suggesting their potential as prognostic biomarkers. Abnormal CTU2 expression in tumors is associated with alterations in immune cell infiltration, immune evasion, and immunotherapy response. CTU2 may contribute to several key cancer-related pathways and biological processes. Mechanistically, CTU2 overexpression is likely driven by DNA copy number amplification and DNA methylation alterations. USF1 has been identified as one of the transcription factors regulating CTU2.ConclusionsCTU2 may serve as a valuable prognostic and immunotherapeutic biomarker across multiple cancer types, providing new insights into tumor treatment strategies and immune evasion from the perspective of tRNA modifications.